Protracted Neoarchean high-temperature–moderate-pressure metamorphism recorded in the granulite-facies Katanning Gold Deposit, Southwest Yilgarn Craton, Western Australia - Jonathan Garcia; Naomi Tucker; Margaux Le Vaillant; Helen B. McFarlane; Laure Martin; Kai Rankenburg; Marco Fiorentini (Precambrian Research, 2026)

Corrigendum to “Estimating irrigation consumptive use for the conterminous United States: coupling satellite-sourced estimates of actual evapotranspiration with a national hydrologic model” [J. Hydrol. 662 (2025) 133909] - Donald J. Martin; Richard G. Niswonger; R.Steve Regan; Justin L. Huntington; Thomas Ott; Charles Morton; Gabriel B. Senay; MacKenzie Friedrichs; Forrest S. Melton; Jonathan Haynes; Wesley Henson; Amy Read; et al. (Journal of Hydrology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Quadriceps mitochondrial DNA quantity, quality, and gene expression after 2 years of calorie restriction: exploratory results from the CALERIE trial - Jayanta K. Das; Yu Zhang; Leanne M. Redman; Corby K. Martin; Sai Krupa Das; Susan B. Racette; Allen Herbst; Nianjun Liu; David B. Allison; Debbie McKenzie; Judd M. Aiken; Steve Horvath; et al. (GeroScience, 2026)
The Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy (CALERIE)™ trial was a randomized, 2-year controlled trial of caloric restriction (CR) versus an ad libitum (AL) control condition in nonobese humans. We performed exploratory analyses of muscle mitochondrial DNA (mtDNA) integrity, one element of mitochondrial quality. Our aims were to assess the feasibility of this approach, explore associations to inform future hypotheses, estimate effect sizes and statistical power for subsequent studies, and contribute additional data to the CALERIE database. We used droplet digital PCR to quantitate the copy numbers of nuclear DNA, mtDNA, and mtDNA deletion mutations in remnant total DNA samples extracted from quadriceps biopsies at baseline ( n = 93), 12 months ( n = 44), and 24 months ( n = 31). MtDNA copy number and mutation frequency were correlated with existing gene expression data from the same muscle biopsies. MtDNA copy number was lower in females ( p = 0.0005) and declined over time ( p = 0.0001), with no statistically significant differences observed for CR versus AL ( p = 0.2898) or age across both groups ( p = 0.4644). Baseline copy number correlated positively with baseline physiological measures including fat-free mass ( r = 0.43, p = 2e−05), self-reported energy intake ( r = 0.34, p = 0.00077), resting metabolic rate ( r = 0.42, p = 0.00261), total energy expenditure ( r = 0.31, p = 0.00261), and V̇O₂max ( r = 0.41, p = 1e−04), and with gene expression related to mitochondrial function, while showing negative correlations with nuclear genome maintenance, RNA splicing, and ribosomes. MtDNA mutation frequency increased with age ( p = 0.0041) and showed a weak negative correlation with V̇O 2 max ( r = −0.23, p = 3e−05). MtDNA mutation frequency was not statistically different with CR. Mutation frequency was positively correlated with gene expression changes in inflammation and negatively correlated with protein translation. We observed that, as expected, mtDNA copy number declined over time, was lower in females, and correlated with metabolic measures and mitochondrial gene expression, suggesting its potential utility as a marker of metabolic health. These findings contribute to understanding mitochondrial adaptations to CR and highlight potential benefits of CR interventions. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The critical zone thickness: spatial heterogeneity and controlling factors in China - Jinke Chen; Tao Zhang; Jonathan B. Martin; Nataša Ravbar; Alena Gessert; Eko Haryono; Jianhong Li; Daoxian Yuan; Junbing Pu (Science Bulletin, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Estimating irrigation consumptive use for the conterminous United States: coupling satellite-sourced estimates of actual evapotranspiration with a national hydrologic model - Donald J. Martin; Richard G. Niswonger; R. Steve Regan; Justin L. Huntington; Thomas Ott; Charles Morton; Gabriel B. Senay; MacKenzie Friedrichs; Forrest S. Melton; Jonathan Haynes; Wesley Henson; Amy Read; et al. (Journal of Hydrology, 2025)

Six Decades of Losses and Gains in Alpha Diversity of European Plant Communities - Gabriele Midolo; Adam Thomas Clark; Milan Chytrý; Franz Essl; Stefan Dullinger; Ute Jandt; Helge Bruelheide; Olivier Argagnon; Idoia Biurrun; Alessandro Chiarucci; Renata Ćušterevska; Pieter De Frenne; et al. (Ecology Letters, 2025)
Biodiversity change forecasts rely on long‐term time series, but such data are often scarce in space and time. Here, we interpolated spatiotemporal changes in species richness using a new method based on machine learning that does not require temporal replication at sites. Using 698,692 one‐time sampled vegetation plots, we estimated trends in vascular plant alpha diversity across Europe and validated our approach against 22,852 independent time series. We found an overall near‐zero net change in species richness between 1960 and 2020. However, species richness generally declined from 1960 to 1980 and increased from 2000 to 2020 across habitats. Declines were most pronounced in forests, but trends varied across habitats and regions, with overall increases at higher latitudes and elevations, and declines or stable trends elsewhere. Our findings demonstrate how data without temporal replication can be used to reveal context‐dependent biodiversity dynamics, underscoring their importance for conservation and management.

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

High‐resolution analysis of sediments from Eighteen Mile Swamp (eastern Australia) records its transition from a fluctuating coastal lagoon to stable freshwater swamp - Jonathan C. Marshall; John Tibby; Patrick Moss; Hailey Martin; Allen Gontz; Annie Lau; Geraldine E. Jacobsen; Haidee Cadd; Patricia S. Gadd; Peter Negus; GLENN B. Mcgregor; Harald Hofmann; et al. (Journal of Quaternary Science, 2025)
This research documents the paleoenvironmental evolution of Eighteen Mile Swamp on North Stradbroke Island (Minjerribah), Australia, from oscillating coastal lagoon into stable freshwater swamp over the last ca. 1600 years. We analyzed multiple sediment cores via physical description, acid sulfate soil assays, particle size analysis, diatom and pollen assemblages, photosynthetic pigment content, and Itrax XRF spectrometry, alongside ground‐penetrating radar cross‐sections. This provided a detailed ecological, geochemical and chronological framework, derived from radiocarbon, Pu and 210 Pb dating, for the wetland's evolution. Results indicate spatial complexity in the timing of a pronounced shift in sedimentary conditions between ca. 300 and 1000 years ago, from estuarine mud to freshwater peat, marked by abrupt chemical and ecological changes. Unexpectedly, there were at least three and potentially many periods of dominant freshwater influence within the primarily estuarine phase, suggesting episodic estuarine closure and freshening by groundwater influx. Results provide critical insights into the complex response of subtropical wetland systems to environmental change, emphasizing the importance of interdisciplinary approaches in understanding both sedimentologic and geomorphic responses in coastal wetlands, and their potential vulnerability to future climate change. The study of Eighteen Mile Swamp is significant as it provides a detailed paleoenvironmental reconstruction that documents the wetland's evolving nature over the past two millennia. This research highlights the importance of understanding historical responses of wetlands to environmental changes, which helps inform their current and future management, conservation and restoration efforts, particularly in the context of climate change and human impacts. This study also serves as a tribute to the late Lynda Petherick, acknowledging her contributions in this field.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Maternal pre-pregnancy BMI influences the associations between bisphenol and phthalate exposures and maternal weight changes and fat accumulation - Nathalie Irvine; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Jiaying Liu; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey; Gillian England-Mason; B.J. Kaplan; C.J. Field; et al. (Environmental Research, 2024)

Sources of limestone dissolution from surface water-groundwater interaction in the carbonate critical zone - Andrew Oberhelman; Jonathan B. Martin; Madison K. Flint (Chemical Geology, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Proximity to an old-growth forest edge and ectomycorrhizal tree islands enhance ectomycorrhizal fungal colonization of Betula lenta L. (black birch) seedlings in secondary forest soils - Andrew M. Cortese; John E. Drake; Martin Dovciak; Jonathan B. Cohen; Thomas R. Horton (Plant and Soil, 2023)

Methane cycling in the carbonate critical zone - Andrew Oberhelman; Jonathan B. Martin; Madison K. Flint (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

ForestClim —Bioclimatic variables for microclimate temperatures of European forests - Stef Haesen; Jonas J. Lembrechts; Pieter De Frenne; Jonathan Lenoir; Juha Aalto; Michael B. Ashcroft; Martin Kopecký; Miska Luoto; Ilya Maclean; Ivan Nijs; Pekka Niittynen; Johan van den Hoogen; et al. (Global Change Biology, 2023)
Microclimate research gained renewed interest over the last decade and its importance for many ecological processes is increasingly being recognized. Consequently, the call for high‐resolution microclimatic temperature grids across broad spatial extents is becoming more pressing to improve ecological models. Here, we provide a new set of open‐access bioclimatic variables for microclimate temperatures of European forests at 25 × 25 m 2 resolution.

Traits of dominant plant species drive normalized difference vegetation index in grasslands globally - Thore Engel; Helge Bruelheide; Daniela Hoss; Francesco M. Sabatini; Jan Altman; Mohammed A. S. Arfin‐Khan; Erwin Bergmeier; Tomáš Černý; Milan Chytrý; Matteo Dainese; Jürgen Dengler; Jiri Dolezal; et al. (Global Ecology and Biogeography, 2023)
Aim Theoretical, experimental and observational studies have shown that biodiversity–ecosystem functioning (BEF) relationships are influenced by functional community structure through two mutually non‐exclusive mechanisms: (1) the dominance effect (which relates to the traits of the dominant species); and (2) the niche partitioning effect [which relates to functional diversity (FD)]. Although both mechanisms have been studied in plant communities and experiments at small spatial extents, it remains unclear whether evidence from small‐extent case studies translates into a generalizable macroecological pattern. Here, we evaluate dominance and niche partitioning effects simultaneously in grassland systems world‐wide. Location Two thousand nine hundred and forty‐one grassland plots globally. Time period 2000–2014. Major taxa studied Vascular plants. Methods We obtained plot‐based data on functional community structure from the global vegetation plot database “sPlot”, which combines species composition with plant trait data from the “TRY” database. We used data on the community‐weighted mean (CWM) and FD for 18 ecologically relevant plant traits. As an indicator of primary productivity, we extracted the satellite‐derived normalized difference vegetation index (NDVI) from MODIS. Using generalized additive models and deviation partitioning, we estimated the contributions of trait CWM and FD to the variation in annual maximum NDVI, while controlling for climatic variables and spatial structure. Results Grassland communities dominated by relatively tall species with acquisitive traits had higher NDVI values, suggesting the prevalence of dominance effects for BEF relationships. We found no support for niche partitioning for the functional traits analysed, because NDVI remained unaffected by FD. Most of the predictive power of traits was shared by climatic predictors and spatial coordinates. This highlights the importance of community assembly processes for BEF relationships in natural communities. Main conclusions Our analysis provides empirical evidence that plant functional community structure and global patterns in primary productivity are linked through the resource economics and size traits of the dominant species. This is an important test of the hypotheses underlying BEF relationships at the global scale.

Overview of temporary radioxenon background measurement campaigns conducted for the CTBTO between 2008 and 2018 - Jonathan Baré; Abdelhakim Gheddou; Martin B. Kalinowski (Journal of Environmental Radioactivity, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Novel Exosome Biomarker Candidates for Alzheimer’s Disease Unravelled Through Mass Spectrometry Analysis - Tânia Soares Martins; Rui Marçalo; Cristóvão B. da Cruz e Silva; Dário Trindade; José Catita; Francisco Amado; Tânia Melo; Ilka Martins Rosa; Jonathan Vogelgsang; Jens Wiltfang; Odete A. B. da Cruz e Silva; Ana Gabriela Henriques (Molecular Neurobiology, 2022)
Exosomes are small extracellular vesicles (EVs) present in human biofluids that can transport specific disease-associated molecules. Consequently blood-derived exosomes have emerged as important peripheral biomarker sources for a wide range of diseases, among them Alzheimer’s disease (AD). Although there is no effective cure for AD, an accurate diagnosis, relying on easily accessible peripheral biofluids, is still necessary to discriminate this disease from other dementias, test potential therapies and even monitor rate of disease progression. The ultimate goal is to produce a cost-effective and widely available alternative, which can also be employed as a first clinical screen. In this study, EVs with exosome-like characteristics were isolated from serum of Controls and AD cases through precipitation- and column-based methods, followed by mass spectrometry analysis. The resulting proteomes were characterized by Gene Ontology (GO) and multivariate analyses. Although GO terms were similar for exosomes’ proteomes of Controls and ADs, using both methodologies, a clear segregation of disease cases was obtained when using the precipitation-based method. Nine significantly different abundant proteins were identified between Controls and AD cases, representing putative biomarker candidate targets. Among them are AACT and C4BPα, two Aβ-binding proteins, whose exosome levels were further validated in individuals from independent cohorts using antibody-based approaches. The findings discussed represent an important contribution to the identification of novel exosomal biomarker candidates useful as potential blood-based tools for AD diagnosis.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

ForestTemp – Sub‐canopy microclimate temperatures of European forests - Stef Haesen; Jonas J. Lembrechts; Pieter De Frenne; Jonathan Lenoir; Juha Aalto; Michael B. Ashcroft; Martin Kopecký; Miska Luoto; Ilya Maclean; Ivan Nijs; Pekka Niittynen; Johan van den Hoogen; et al. (Global Change Biology, 2021)
Ecological research heavily relies on coarse‐gridded climate data based on standardized temperature measurements recorded at 2 m height in open landscapes. However, many organisms experience environmental conditions that differ substantially from those captured by these macroclimatic (i.e. free air) temperature grids. In forests, the tree canopy functions as a thermal insulator and buffers sub‐canopy microclimatic conditions, thereby affecting biological and ecological processes. To improve the assessment of climatic conditions and climate‐change‐related impacts on forest‐floor biodiversity and functioning, high‐resolution temperature grids reflecting forest microclimates are thus urgently needed. Combining more than 1200 time series of in situ near‐surface forest temperature with topographical, biological and macroclimatic variables in a machine learning model, we predicted the mean monthly offset between sub‐canopy temperature at 15 cm above the surface and free‐air temperature over the period 2000–2020 at a spatial resolution of 25 m across Europe. This offset was used to evaluate the difference between microclimate and macroclimate across space and seasons and finally enabled us to calculate mean annual and monthly temperatures for European forest understories. We found that sub‐canopy air temperatures differ substantially from free‐air temperatures, being on average 2.1°C (standard deviation ± 1.6°C) lower in summer and 2.0°C higher (±0.7°C) in winter across Europe. Additionally, our high‐resolution maps expose considerable microclimatic variation within landscapes, not captured by the gridded macroclimatic products. The provided forest sub‐canopy temperature maps will enable future research to model below‐canopy biological processes and patterns, as well as species distributions more accurately.

Campylobacterota dominate the microbial communities in a tropical karst subterranean estuary, with implications for cycling and export of nitrogen to coastal waters - Laibin Huang; Hee‐Sung Bae; Caitlin Young; Andrea J. Pain; Jonathan B. Martin; Andrew Ogram (Environmental Microbiology, 2021)
Summary Subterranean estuaries (STEs), the zones in which seawater and subsurface groundwater mix, are recognized as hotspots for biogeochemical reactions; however, little is known of the microbial communities that control many of those reactions. This study investigated the potential functions of microbes inhabiting a cenote and an offshore submarine spring (Pargos) in the near‐coastal waters of the Yucatan Peninsula, Mexico. The inland cenote (Cenote Siete Bocas; C7B) is characterized by a chemocline that is host to an array of physicochemical gradients associated with microbial activities. The chemocline includes an increasing gradient in sulfide concentrations with depth and a decreasing gradient in nitrate concentrations. The microbial community within the chemocline was dominated by Sulfurimonas and Sulfurovum of the Campylobacteria , which are likely responsible for sulfide oxidation coupled with nitrate reduction. Although C7B has not been directly connected with Pargos Spring, water discharging from the spring has physicochemical characteristics and microbial community structures similar to C7B, strongly suggesting biogeochemical processing in the STE impacts groundwater composition prior to discharge. This work yields insight into the microbial communities and biogeochemical reactions in STEs in karstic aquifers and provides evidence for the importance of Campylobacteria in controlling nitrate concentrations exported to marine springs.

San Antonio Nathan Shock Center: your one-stop shop for aging research - Adam B. Salmon; James F. Nelson; Jonathan A. L. Gelfond; Martin Javors; Brett Ginsburg; Marisa Lopez-Cruzan; Veronica Galvan; Elizabeth Fernandez; Nicolas Musi; Yuji Ikeno; Gene Hubbard; James Lechleiter; et al. (GeroScience, 2021)

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Biogeochemical and Hydrological Drivers of Heterogeneous Nutrient Exports From Subterranean Estuaries - Andrea J. Pain; Jonathan B. Martin; Caitlin R. Young (Frontiers in Marine Science, 2021)
Submarine groundwater discharge (SGD) to coastal zones contributes terrestrial freshwater and nutrients that may support harmful algal blooms (HABs). The magnitude of nutrient exports via SGD depends on volumes of fresh groundwater discharge, its chemical composition, and modifications by biogeochemical processing within subterranean estuaries. Thus, the ability to upscale SGD exports requires knowing the range of chemical composition of inland groundwater and how those compositions may be transformed as fresh and saltwater mix within subterranean estuaries. These processes may create heterogeneous magnitudes of solute exports, even at small spatial scales, and such heterogeneities have rarely been assessed for regional or global SGD nutrient export estimates. To evaluate heterogeneity in subterranean estuary processes and nutrient export, we collected seasonal pore water samples in 2015–2016 at three proximal (<20 km) subterranean estuary sites in Indian River Lagoon, FL. Sites have homogenous hydrogeological settings, but differ in land use and coastal features, and include a mangrove site, an urban site, and a site offshore of a natural wetland. All sites exhibit little variation through time in nutrient concentrations and modeled SGD rates. In contrast, each site exhibits significantly different nutrient concentrations of potential fresh groundwater sources, fresh groundwater discharge volumes, and nutrient transformations within subterranean estuaries. Groundwater specific discharge correlates with nutrient concentrations, suggesting that higher residence times in the subterranean estuary increase biogeochemical transformations that reduce anthropogenic nutrient loads but increase in situ nutrient sources derived from organic matter remineralization. The differences in transformations lead to SGD nutrient contributions that differ by orders of magnitude between sites and have N:P ratios that are greater than the Redfield ratio (15) for the mangrove (29) and urban sites (28), but less than the Redfield ratio for the wetland site (8). These results indicate that heterogeneity of both absolute and relative nutrient export via SGD complicates integration of nutrient fluxes across regional coastal zones and evaluations of its impacts to coastal ecosystems. A better understanding of the drivers of heterogeneity, including subterranean estuary processes, land use, coastal topography, and vegetation dynamics could improve assessments of regional nutrient loading and upscaling for estimates of global solute cycles.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data - Aurore A. Maureaud; Romain Frelat; Laurène Pécuchet; Nancy Shackell; Bastien Mérigot; Malin L. Pinsky; Kofi Amador; Sean C. Anderson; Alexander Arkhipkin; Arnaud Auber; Iça Barri; Richard J. Bell; et al. (Global Change Biology, 2021)
Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283,925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Extended Pelagic Life in a Bathybenthic Octopus - Roger Villanueva; Vladimir V. Laptikhovsky; Stuart B. Piertney; Fernando Ángel Fernández-Álvarez; Martin A. Collins; Jonathan D. Ablett; Alejandro Escánez (Frontiers in Marine Science, 2020)
Planktonic stages of benthic octopuses can reach relatively large sizes in some species, usually in oceanic, epipelagic waters while living as part of the macroplankton. These young octopuses appear to delay settlement on the seabed for an undetermined period of time that is probably longer than for those octopus paralarvae living in coastal, neritic waters. The reason for this delay is unknown and existing information about their biology is very scarce. Here we report on the presence of juvenile and subadult forms of the bathybenthic octopus Pteroctopus tetracirrhus in oceanic waters of the South and North Atlantic and its association with the pyrosomid species Pyrosoma atlanticum , apparently used by the octopus as a refuge or shelter. The relatively large size of the P. tetracirrhus living in oceanic waters as the individuals reported here, together with the morphological characteristics of this bathybenthic species including its gelatinous body, minute suckers embedded in swollen skin and the deep interbrachial web, indicates that P. tetracirrhus may be considered a model of a transitional octopus species that is colonizing the pelagic environment by avoiding descending to the bathyal benthos. This process seems to occur in the same way as in the supposed origin of the ctenoglossan holopelagic octopods of the families Amphitretidae, Bolitaenidae, and Vitreledonellidae, which have arisen via neoteny from the planktonic paralarval stages of benthic octopuses.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Fundamental drivers of dissolved organic matter composition across an Arctic effective precipitation gradient - Anne M. Kellerman; Ana Arellano; David C. Podgorski; Ellen E. Martin; Jonathan B. Martin; Kelly M. Deuerling; Thomas S. Bianchi; Robert G. M. Spencer (Limnology and Oceanography, 2020)
The standard model for aquatic ecosystems is to link hydrologic connectivity to dissolved organic carbon (DOC) concentration and dissolved organic matter (DOM) composition and, ultimately, reactivity. Studies across effective precipitation gradients have been suggested as models for predicting how carbon cycling will change in Arctic aquatic ecosystems with projected drying (i.e., reduced hydrologic connectivity). To evaluate links between DOM dynamics and hydrologic connectivity, 41 stream samples from Greenland were analyzed across an effective precipitation gradient for DOM optical properties and elemental composition using ultrahigh‐resolution mass spectrometry. Sites with negative effective precipitation and decreased hydrologic connectivity exhibited elevated specific conductivity (SpC) and DOC concentrations as well as DOM composition indicative of decreased hydrologic connectivity, for example, lower aromaticity, assessed using carbon‐specific UV absorbance at 254 nm, decreased relative abundances of polyphenolic and condensed aromatic compounds, and increased relative abundances of highly unsaturated and phenolic compounds. Allochthonous inputs decreased as the summer progressed as exhibited by decreases in aromatic compounds. A decrease in molecular richness and N‐containing compounds coincided with the decrease in allochthonous inputs. DOC concentrations increased over the summer but more slowly than SpC, suggesting degradation processes outweighed combined evapoconcentration and production. The patterns in DOM composition suggest evapoconcentration and photodegradation are dominant controls. However, when hydrologic connectivity was high, regardless of effective precipitation, DOM reflected allochthonous sources such as snowmelt‐fed wetlands. These results highlight the challenges of modeling carbon cycling in aquatic ecosystems across effective precipitation gradients, particularly those with strong seasonality and regional variability in hydrologic inputs.

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Sources and sinks of CO 2 and CH 4 in siliciclastic subterranean estuaries - Andrea J. Pain; Jonathan B. Martin; Caitlin R. Young (Limnology and Oceanography, 2019)
Anthropogenic production of greenhouse gases (GHGs) has intensified the need to constrain estimates of natural atmospheric sources from both terrestrial and marine systems. Estuaries are known sources of carbon dioxide (CO 2 ) and methane (CH 4 ); however, less is known about GHG dynamics in subterranean estuaries (STEs). We evaluate CO 2 and CH 4 dynamics in three proximal STEs bordering Indian River Lagoon, Florida, where groundwater flows through siliciclastic sediments with minor carbonate mineral contents. Although the three STEs have similar mineralogical and flow characteristics, CO 2 and CH 4 concentrations vary by orders of magnitude. Nonconservative mixing of both gases is observed, and CH 4 is generally produced while CO 2 is sequestered. The extent of methanogenesis is linked to the redox potential of inflowing groundwaters, as well as degree of CH 4 oxidation, which results mostly from anaerobic oxidation of methane. Methane concentrations vary by orders of magnitude, and stable isotopic signatures suggest differences in the microbial production pathway between sites. CO 2 is sequestered due to the production of alkalinity relative to dissolved inorganic carbon, which occurs both through rapid CaCO 3 dissolution at the shoreline as low‐pH groundwater from the siliciclastic aquifer interacts with carbonate minerals in lagoon sediments, as well as redox reactions, particularly sulfate reduction and denitrification. These results demonstrate a high variability in CO 2 and CH 4 concentrations, and thus fluxes, even among geographically constrained and hydrogeologically similar STEs. Although STEs are sources of both CO 2 and CH 4 to surface waters, the variability of production and consumption complicates global estimates of GHG fluxes from STEs.

Organic matter quantity and quality across salinity gradients in conduit‐ vs. diffuse flow‐dominated subterranean estuaries - Andrea J. Pain; Jonathan B. Martin; Caitlin R. Young; Laibin Huang; Arnoldo Valle‐Levinson (Limnology and Oceanography, 2019)
Submarine groundwater discharge (SGD) is a source of water and bioreactive solutes to coastal zones but may be modified by organic matter (OM) remineralization dynamics within subterranean estuaries (STEs). We hypothesize that bioreactive solute fluxes should depend on water residence time in STEs, but links between OM transformations and residence time in STEs are poorly characterized. To test this hypothesis, we compare dissolved OM (DOM) quantity and quality in two hydrologically distinct STE systems: a reef lagoon on the east coast of the Yucatan Peninsula, Mexico, where semidiurnal mixing in submarine springs of a carbonate karst aquifer results in short residence times, and a barrier lagoon on the east coast of Florida, where slow flow through siliciclastic sediments results in long residence times. We measured dissolved organic carbon concentrations and characterized colored DOM (CDOM) with ultraviolet spectroscopy and fluorescence combined with Parallel Factor Analysis. Both sites exhibit similar shifts in OM quality with salinity and reflect a marine source of labile OM to the STEs. Nonconservative mixing and CDOM production occurs at all sites but the long water residence times in the siliciclastic STEs cause orders of magnitude greater production than the carbonate STE. Consistent CDOM production across sites with disparate characteristics indicates that STEs are common sources of CDOM to surface water. However, observed variation in the magnitudes of CDOM production indicates that estimating global, and even regional, solute fluxes associated with SGD will be complicated by hydrologic control on extents of OM remineralization.

Diel-scale variation of dissolved inorganic carbon during a rainfall event in a small karst stream in southern China - Junbing Pu; Jianhong Li; Tao Zhang; Jonathan B. Martin; Mitra B. Khadka; Daoxian Yuan (Environmental Science and Pollution Research, 2019)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Effects of short‐term variations in sea level on dissolved oxygen in a coastal karst aquifer, Quintana Roo, Mexico - Caitlin Young; Jonathan B. Martin; Jackie Branyon; Andrea Pain; Arnoldo Valle‐Levinson; Ismael Mariño‐Tapia; Mario Rebolledo Vieyra (Limnology and Oceanography, 2018)
Sea‐level rise should cause salt‐water intrusion into coastal aquifers and limit fresh submarine groundwater discharge. Pargos Spring offshore of Puerto Morelos, Quintana Roo, Mexico, intermittently discharges brackish water and allows intrusion of lagoon water with seawater salinity to the aquifer. Lagoon water intrusion occurred when sea level was > 0.08 m above mean observed values during the study period. Salt water intrusion will be permanent within a few decades at the current eustatic sea‐level rise rate of ∼ 3 mm/yr. A mixing model demonstrates that oxygen dissolved in the lagoon water is reduced as it intrudes the spring. Dissolved oxygen (DO) reduction is greater at the spring vent than at sensors ∼ 10 m inside the conduit, reflecting rapid reaction kinetics. DO reduction results from organic carbon remineralization, which also releases N and P to the water. Increased frequency of intrusion events or continuous intrusion may alter microbially mediated biogeochemical reactions, thereby increasing aquifer vulnerability to sea‐level rise.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Acute liver effects, disposition and metabolic fate of [14C]-fenclozic acid following oral administration to normal and bile-cannulated male C57BL/6J mice - Kathryn Pickup; Scott Martin; Elizabeth A. Partridge; Huw B. Jones; Jonathan Wills; Tim Schulz-Utermoehl; Alan McCarthy; Alison Rodrigues; Chris Page; Kerry Ratcliffe; Sunil Sarda; Ian D. Wilson (Archives of Toxicology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

The regional species richness and genetic diversity of A rctic vegetation reflect both past glaciations and current climate - Lærke Stewart; Inger G. Alsos; Christian Bay; Amy L. Breen; Christian Brochmann; Noémie Boulanger‐Lapointe; Olivier Broennimann; Helga Bültmann; Peder Klith Bøcher; Christian Damgaard; Fred J. A. Daniëls; Dorothee Ehrich; et al. (Global Ecology and Biogeography, 2016)
Aim The A rctic has experienced marked climatic differences between glacial and interglacial periods and is now subject to a rapidly warming climate. Knowledge of the effects of historical processes on current patterns of diversity may aid predictions of the responses of vegetation to future climate change. We aim to test whether plant species and genetic diversity patterns are correlated with time since deglaciation at regional and local scales. We also investigate whether species richness is correlated with genetic diversity in vascular plants. Location Circumarctic. Methods We investigated species richness of the vascular plant flora of 21 floristic provinces and examined local species richness in 6215 vegetation plots distributed across the A rctic. We assessed levels of genetic diversity inferred from amplified fragment length polymorphism variation across populations of 23 common A rctic species. Correlations between diversity measures and landscape age (time since deglaciation) as well as variables characterizing current climate were analysed using spatially explicit simultaneous autoregressive models. Results Regional species richness of vascular plants and genetic diversity were correlated with each other, and both showed a positive relationship with landscape age. Plot species richness showed differing responses for vascular plants, bryophytes and lichens. At this finer scale, the richness of vascular plants was not significantly related to landscape age, which had a small effect size compared to the models of bryophyte and lichen richness. Main conclusion Our study suggests that imprints of past glaciations in A rctic vegetation diversity patterns at the regional scale are still detectable today. Since A rctic vegetation is still limited by post‐glacial migration lag, it will most probably also exhibit lags in response to current and future climate change. Our results also suggest that local species richness at the plot scale is more determined by local habitat factors.

Non-native and native organisms moving into high elevation and high latitude ecosystems in an era of climate change: new challenges for ecology and conservation - Aníbal Pauchard; Ann Milbau; Ann Albihn; Jake Alexander; Treena Burgess; Curtis Daehler; Göran Englund; Franz Essl; Birgitta Evengård; Gregory B. Greenwood; Sylvia Haider; Jonathan Lenoir; et al. (Biological Invasions, 2016)

Disjunct populations of E uropean vascular plant species keep the same climatic niches - Safaa Wasof; Jonathan Lenoir; Per Arild Aarrestad; Inger Greve Alsos; W. Scott Armbruster; Gunnar Austrheim; Vegar Bakkestuen; H. John B. Birks; Kari Anne Bråthen; Olivier Broennimann; Jörg Brunet; Hans Henrik Bruun; et al. (Global Ecology and Biogeography, 2015)
Aim Previous research on how climatic niches vary across species ranges has focused on a limited number of species, mostly invasive, and has not, to date, been very conclusive. Here we assess the degree of niche conservatism between distant populations of native alpine plant species that have been separated for thousands of years. Location European A lps and F ennoscandia. Methods Of the studied pool of 888 terrestrial vascular plant species occurring in both the A lps and F ennoscandia, we used two complementary approaches to test and quantify climatic‐niche shifts for 31 species having strictly disjunct populations and 358 species having either a contiguous or a patchy distribution with distant populations. First, we used species distribution modelling to test for a region effect on each species' climatic niche. Second, we quantified niche overlap and shifts in niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) within a bi‐dimensional climatic space. Results Only one species (3%) of the 31 species with strictly disjunct populations and 58 species (16%) of the 358 species with distant populations showed a region effect on their climatic niche. Niche overlap was higher for species with strictly disjunct populations than for species with distant populations and highest for arctic–alpine species. Climatic niches were, on average, wider and located towards warmer and wetter conditions in the Alps. Main conclusion Climatic niches seem to be generally conserved between populations that are separated between the A lps and F ennoscandia and have probably been so for 10,000–15,000 years. Therefore, the basic assumption of species distribution models that a species' climatic niche is constant in space and time – at least on time scales 10 4 years or less – seems to be largely valid for arctic–alpine plants.

Insights on surface-water/groundwater exchange in the upper Floridan aquifer, north-central Florida (USA), from streamflow data and numerical modeling - James E. Sutton; Elizabeth J. Screaton; Jonathan B. Martin (Hydrogeology Journal, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Insect attraction to herbivore-induced beech volatiles under different forest management regimes - Martin M. Gossner; Wolfgang W. Weisser; Jonathan Gershenzon; Sybille B. Unsicker (Oecologia, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Predicting species distributions for conservation decisions - Antoine Guisan; Reid Tingley; John B. Baumgartner; Ilona Naujokaitis‐Lewis; Patricia R. Sutcliffe; Ayesha I. T. Tulloch; Tracey J. Regan; Lluis Brotons; Eve McDonald‐Madden; Chrystal Mantyka‐Pringle; Tara G. Martin; Jonathan R. Rhodes; et al. (Ecology Letters, 2013)
Species distribution models (SDMs) are increasingly proposed to support conservation decision making. However, evidence of SDMs supporting solutions for on‐ground conservation problems is still scarce in the scientific literature. Here, we show that successful examples exist but are still largely hidden in the grey literature, and thus less accessible for analysis and learning. Furthermore, the decision framework within which SDMs are used is rarely made explicit. Using case studies from biological invasions, identification of critical habitats, reserve selection and translocation of endangered species, we propose that SDMs may be tailored to suit a range of decision‐making contexts when used within a structured and transparent decision‐making process. To construct appropriate SDMs to more effectively guide conservation actions, modellers need to better understand the decision process, and decision makers need to provide feedback to modellers regarding the actual use of SDMs to support conservation decisions. This could be facilitated by individuals or institutions playing the role of ‘translators’ between modellers and decision makers. We encourage species distribution modellers to get involved in real decision‐making processes that will benefit from their technical input; this strategy has the potential to better bridge theory and practice, and contribute to improve both scientific knowledge and conservation outcomes.

Local temperatures inferred from plant communities suggest strong spatial buffering of climate warming across N orthern E urope - Jonathan Lenoir; Bente Jessen Graae; Per Arild Aarrestad; Inger Greve Alsos; W. Scott Armbruster; Gunnar Austrheim; Claes Bergendorff; H. John B. Birks; Kari Anne Bråthen; Jörg Brunet; Hans Henrik Bruun; Carl Johan Dahlberg; et al. (Global Change Biology, 2013)
Recent studies from mountainous areas of small spatial extent ( 2 ) suggest that fine‐grained thermal variability over tens or hundreds of metres exceeds much of the climate warming expected for the coming decades. Such variability in temperature provides buffering to mitigate climate‐change impacts. Is this local spatial buffering restricted to topographically complex terrains? To answer this, we here study fine‐grained thermal variability across a 2500‐km wide latitudinal gradient in N orthern E urope encompassing a large array of topographic complexities. We first combined plant community data, E llenberg temperature indicator values, locally measured temperatures (LmT) and globally interpolated temperatures (GiT) in a modelling framework to infer biologically relevant temperature conditions from plant assemblages within 2 units (community‐inferred temperatures: CiT). We then assessed: (1) CiT range (thermal variability) within 1‐km 2 units; (2) the relationship between CiT range and topographically and geographically derived predictors at 1‐km resolution; and (3) whether spatial turnover in CiT is greater than spatial turnover in GiT within 100‐km 2 units. E llenberg temperature indicator values in combination with plant assemblages explained 46–72% of variation in LmT and 92–96% of variation in GiT during the growing season ( J une, J uly, A ugust). Growing‐season CiT range within 1‐km 2 units peaked at 60–65°N and increased with terrain roughness, averaging 1.97 °C ( SD = 0.84 °C) and 2.68 °C ( SD = 1.26 °C) within the flattest and roughest units respectively. Complex interactions between topography‐related variables and latitude explained 35% of variation in growing‐season CiT range when accounting for sampling effort and residual spatial autocorrelation. Spatial turnover in growing‐season CiT within 100‐km 2 units was, on average, 1.8 times greater (0.32 °C km −1 ) than spatial turnover in growing‐season GiT (0.18 °C km −1 ). We conclude that thermal variability within 1‐km 2 units strongly increases local spatial buffering of future climate warming across N orthern E urope, even in the flattest terrains.

Erratum to: Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Interactions of diffuse and focused allogenic recharge in an eogenetic karst aquifer (Florida, USA) - Abigail L. Langston; Elizabeth J. Screaton; Jonathan B. Martin; Vincent Bailly-Comte (Hydrogeology Journal, 2012)

Hydrologic and biotic influences on nitrate removal in a subtropical spring‐fed river - James B. Heffernan; Matthew J. Cohen; Thomas K. Frazer; Ray G. Thomas; Travis J. Rayfield; Jason Gulley; Jonathan B. Martin; Joseph J. Delfino; Wendy D. Graham (Limnology and Oceanography, 2010)
We use a long‐term chemical and hydrologic record in combination with longitudinal sampling and high‐frequency nitrate (NO 3 ‐ ) measurements from in situ sensors to describe temporal and spatial patterns of nitrogen (N) inputs and removal in the spring‐fed Ichetucknee River (Columbia County, Florida) and to determine the hydrological, geomorphic, and biological factors that influence those dynamics. Over a 20‐yr period of record, NO 3 ‐N removal averaged 118 kg N d ‐1 (0.77 g N m ‐2 d ‐1 ) over the upper 5 km of the Ichetucknee River. Three independent estimates of gross autotrophicNassimilation (from gross primary production, diel NO 3 ‐ variation, and standing biomass) agreed closely but accounted for less than 20% of observed N removal. Longitudinal surveys indicate negligible or negative dissolved organic nitrogen and ammonium (NH 4 + ) production, suggesting that denitrification is the predominant mechanism of N removal in this river. A positive relationship between discharge and the magnitude of NO 3 ‐N removal shows that interactions with the surrounding floodplain exert considerable influence at high flows, and longitudinal NO 3 ‐ patterns indicate that N removal may be influenced by channel morphology. These results suggest a greater role for dissimilatory processes and hydrologic connectivity with hyporheic and floodplain sediments than has been previously recognized in highly productive spring‐fed rivers of north Florida. While hydrologic variation is the primary determinant of variation in NO 3 ‐ removal within the Ichetucknee River, comparison across systems indicates that biotic characteristics can cause significant deviation from predictions based on purely physical models of relationships between river size and N removal.

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Episodic high intensity mixing events in a subterranean estuary: Effects of tropical cyclones - Christopher G. Smith; Jaye E. Cable; Jonathan B .Martin (Limnology and Oceanography, 2008)
Hydrostatic balances between fresh and saline groundwater and saline surface water control the physical and chemical framework of subterranean estuaries, but they are responsive to high frequency (waves and tides), low frequency (seasonal recharge patterns), and episodic (storm) events. In this study, we document a salinity and pressure perturbation to the subterranean estuary in east‐central Florida during and after the passage of Tropical Storm Tammy on 04 Oct 2005–05 Oct 2005 and Hurricane Wilma on 24 Oct 2005. These storms reversed hydraulic gradients, forced lagoon water into the aquifer, and shifted the outflow face landward. Salinity at 1.5 m and 2.5 m below a common datum converged on similar values intermediate between fresh and lagoon water salinities. The outflow face reestablished pre‐storm conditions after 80 days at 15 m offshore, but more than 160 days at 30 m offshore, confirming that both the flow field and fluid sources control the position of the subterranean estuary. Episodic, high intensity events could influence the biogeochemical setting of the subterranean estuary and the overlying water body by altering redox conditions in the subterranean estuary during the landward migration of the dispersive mixing zone, increasing short‐term discharge of potentially contaminated groundwater, and/or changing pore fluid residence time within the seepage face and along the mixing zone‐seepage face front.

Changes in markers of muscle damage, inflammation and HSP70 after an Ironman triathlon race - Katsuhiko Suzuki; Jonathan Peake; Kazunori Nosaka; Mitsuharu Okutsu; Chris R. Abbiss; Rob Surriano; David Bishop; Marc J. Quod; Hamilton Lee; David T. Martin; Paul B. Laursen (European Journal of Applied Physiology, 2006)

Disconnects in Evaluating the Relative Effectiveness of Conservation Strategies - Kathryn A. Saterson; Norman L. Christensen; Robert B. Jackson; Randall A. Kramer; Stuart L. Pimm; Martin D. Smith; Jonathan B. Wiener (Conservation Biology, 2004)

Influence of vegetation change on watershed hydrology: implications for paleoclimatic interpretation of lacustrine δ18O records - Michael F. Rosenmeier; David A. Hodell; Mark Brenner; Jason H. Curtis; Jonathan B. Martin; Flavio S. Anselmetti; Daniel Ariztegui; Thomas P. Guilderson (Journal of Paleolimnology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Delayed obsessive-compulsive disorder symptom exacerbation after a single dose of a serotonin antagonist in fluoxetine-treated but not untreated patients - B. D. Greenberg; Jonathan Benjamin; Juliet D. Martin; David Keuler; S.-J. Huang; Margaret Altemus; Dennis L. Murphy (Psychopharmacology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)